Garuda myth-based toponym as a portrait of Indonesian cultural activities in the Solon years - Sukatman; S. M. Fitriyah (Cogent Arts & Humanities)
Name-giving is vital in Indonesian culture. Names of places, oftentimes bestowed by the king, are often associated with the mythology and culture of those residing around the area. Many regional names in Indonesia are associated with King Garuda mythology, manifesting a declaration of the power network. Through an analysis of the results of interviews with site keepers, community leaders, and academician, and observation, this study aims to portray the link between the toponyms and King Garuda mythology. This critical anthropology study brings forward the urgency to develop a complete and accurate cultural narrative related to King Garuda to be developed for educational purposes as well as for the tourism industry. Territorial toponyms highlighted the need for an in-depth study, especially as the catalyst for maintaining national integrity against separatist actions. Indonesia’s ancient heritage requires further investigation with the support of technology, such as isotope layer testing, which future studies need to cover.